Bovine brucellosis in the Manabí province, Ecuador. Study of risk factors - Zambrano Aguayo, Marina Dalila (2016)
A cross-sectional epidemiological study was carried out to determine animal and herd risk factors associated to bovine brucellosis. It was randomly selected 2369 cattle in the Manabí province, Ecuador. In addition, an epidemiological study of ecological type was carried out using 20 positive herds (cases) and 20 negative herds (controls) to the disease. In both studies, an epidemiological survey was conducted to determine the main risk factors associated to the disease. The individual study showed a higher risk of having the disease in animals older than 5 years (p<0.0001) and in females (p<0.05). Herds involved in milk production (p<0.05), those that do not check the aniamls before entering the premises (p<0.05) and those without vaccination (p<0.001) had a higher risk of being affected by the disease. It was also demonstrated that there was a greater probability of having abortions in infected herds than in those unaffected (p<0.02). It is concluded that there was an increased risk of presenting the disease in animals over 5 years old, in dairy herds and in those that do not check the health status of animals prior to the introduction to the farm and in those without vaccination.